DAMPAK EKONOMI POLITIK DARI ITRC – INRA TERHADAP PRODUKTIVITAS KARET ALAM INDONESIA - Lena Anita Sulastri Purba; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This observation explain about effort from gapkindo for increased natural rubber exportthe proction by participants in Indonesia to be able to meet internasional rubber marketneeds.indonesia know as the country who has the big mainland so that in Indonesia mayority ofIndonesia can survive by farming the extent of plantation be a solution for survive one of withfarming .the rubber plant until this time needs it very important rule for daily needs.the kinds ofnatural rubber in Indonesia very diverse and found in Indonesia.the result to the less ofeducation in Indonesia is a one the main factor Indonesia can’t manage a raw materials to be afinishing goods.This observation use theory of internasioanal cooperation.the type of cooperation that isused is cooperation commodity.cooperation commodity do by third asean countries that isThailand, Malaysia and Indonesia . this observation use an analysis, the countries use thequalitative research methods with library.the data source from books, journal and internet.And the last,gapkindo role to productivity of rubber existing in Indonesia give aprotection to participants who production natural source in Indonesia such as community theprivate sector and goverment maximum considered.the effort have been do is condust policy toall participants belong as a production of natural rubber, give a solution in order for rubberplant can produce good rubber latex.that effort can help all participants who the producenatural source existing in Indonesia.Keywords: Natural Rubber, Cooperation Commodity, Rubber Association of Indonesia.